La deshonestidad académica - Taco Suntasig, Estefany Micaela (2016)
The interest of this research was to demonstrate how academic dishonesty can affect the behavior of students school "GENERAL QUISQUIS", at the time of any activity or to perform a test try to copy, they are proving misconduct. Therefore academic dishonesty was diagnosed in students that allow them to improve their academic performance. The methodology used in the research was the field because it was held at the scene, the present study was performed quantitatively through surveys and qualitative through an in-depth interview, through information provided in this document is found that academic dishonesty exists in the educational unit and that a copy or plagiarism is punishable, for this reason we seek to devise strategies, in order to reduce academic fraud in students and also further strengthen ethical and each of them. Dishonesty is a negative value that is involved in society, but what we focus is in education because through this the hardest hit antivalues are students. It is a phenomenon that alters and affects learning and academic performance of students, that way the student does not have the interest to study and go for the easy way out which is the copy. With the implementation of workshops it is to rescue a very important value that is academic honesty for there to be good relations between teachers and students and thus may have study habits and thus no longer have attempted to copy in any curricular activity established by their teachers. In this way students are able to function on their own in any academic activity was formed, so there will be a spontaneous, creative, independent and autonomous childhood.